Development of Smart Ladder Media for Mathematics Material Units of Length for Class II of Karanggayam 2nd State Elementary School - Muhammad Munir (Indonesian Journal of Progressive Pedagogy, 2025)
Mathematics learning at the elementary level often presents difficulties, especially when introducing abstract concepts such as units of length. To overcome these challenges, engaging and concrete instructional media are required to support students’ understanding. This study aimed to develop Smart Ladder learning media for length units by applying the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The research involved media experts, material experts, instructional experts, teachers, and students as respondents. Data were collected through interviews, questionnaires, and pre- and post-test evaluations. Validation results showed scores of 78.12 (good) from media experts, 88.75 (very good) from material experts, and 78.94 (good) from instructional experts. Teacher responses reached 97.36 (very good), while student trials averaged 83.99 (very good), improving from 78.07 in the first trial to 89.92 in the second. Student achievement also increased from an average pre-test score of 54.58 to a post-test score of 84.58. These findings confirm the feasibility and effectiveness of Smart Ladder media, highlighting its novelty in transforming abstract mathematics into tangible, interactive experiences. The study contributes to the field of educational media development, suggesting that similar models can be adapted for other mathematical concepts to enhance meaningful learning at the elementary level.